A letter to Mrs. Roosevelt - De Young, C. Coco. (New York : Dell Yearling, 2000)
Eleven-year-old Margo fulfills a class assignment by writing a letter to Eleanor Roosevelt asking for help to save her family's home during the Great Depression.
"A Yearling book."
Includes bibliographical references (pages 103-105).
750L
Accelerated Reader
Accelerated Reader AR
Keywords: Roosevelt, Eleanor, -- 1884-1962.; Roosevelt, Eleanor, -- 1884-1962.; 1929; Depressions -- 1929 -- United States; Depressions; Families; Families; Schools; Schools; United States; Fiction; Fiction